Effect of pH and Salinity on the Ability of Salmonella Serotypes to Form Biofilm - Petrin, Sara; Mancin, Marzia; Losasso, Carmen; Deotto, Silvia; Olsen, John Elmerdahl; Barco, Lisa (Frontiers in Microbiology, 2022)
Salmonella is a major cause of food-borne infections in Europe, and the majority of human infections are caused by only a few serotypes, among which Salmonella enterica subsp. enterica serotype Enteritidis (hereafter S. Enteritidis) , S.Typhimurium and the monophasic variant of S.Typhimurium. The reason for this is not fully understood, but could include virulence factors as well as increased ability to transfer via the external environment. Formation of biofilm is considered an adaptation strategy used by bacteria to overcome environmental stresses. In order to assess the capability of different Salmonella serotypes to produce biofilm and establish whether this is affected by pH and salinity, 88 Salmonella isolates collected from animal, food and human sources and belonging to 15 serotypes, including those most frequently responsible for human infections, were tested. Strains were grown in tryptic soy broth (TSB), TSB with 4% NaCl pH 4.5, TSB with 10% NaCl pH 4.5, TSB with 4% NaCl pH 7 or TSB with 10% NaCl pH 7, and biofilm production was assessed after 24 h at 37°C using crystal violet staining. A linear mixed effect model was applied to compare results from the different experimental conditions. Among the tested serotypes, S. Dublin showed the greatest ability to form biofilm even at pH 4.5, which inhibited biofilm production in the other tested serotypes. S. Senftenberg and the monophasic variant of S. Typhimurium showed the highest biofilm production in TSB with 10% NaCl pH 7. In general, pH had a high influence on the ability to form biofilm, and most of the tested strains were not able to produce biofilm at pH 4.5. In contrast, salinity only had a limited influence on biofilm production. In general, serotypes causing the highest number of human infections showed a limited ability to produce biofilm in the tested conditions, indicating that biofilm formation is not a crucial factor in the success of these clones.